Biomarcadores do metabolismo da cartilagem e sua relação com as alterações morfológicas, inflamatórias e funcionais: um estudo sobre a lesão condral secundária em joelhos humanos - Franco, Renata Nogueron (2011)
Osteoarthritis (OA), a degenerative joint disease, is one of the most frequent causes of pain in the musculoskeletal system and of the inability to work in Brazil and the world. It is a multifactor, chronic disease, leading to progressive functional inability. It can arise as a result of injuries to structures such as the anterior crossed ligament and/or meniscus (post-traumatic OA), which, in this case, can affect individuals in any age range. The development of osteoarthritis includes multiple changes in the extracellular cartilage matrix, altering the normal morphological configuration of the joint involved, leading to a lack of equilibrium between the synthesis and degradation of products in this matrix. Although OA is not considered primordially as an inflammatory disease, inflammation of the joint has been shown to be a potential amplifier of the degenerative process. Thus the objective of the present study was to analyze potential biological markers in the serum and synovial fluid, and then correlate them with one another and with the morphological, inflammatory and functional alterations found in individuals with chronic injury of the anterior crossed ligament (ACL). The following techniques were used in the study: zymography, to determine the activity of the metallopeptidases 2 and 9 (MMP-2 and MMP-9); an immune-enzymatic assay (ELISA) to determine the presence of systemic and local cytokines; and a manual count of inflammatory cells (mononuclear and polymorphonuclear) by optical microscopy and spectrophotometry, in order to analyze for sulfated glycosaminoglycans (GAGs). The results indicated joint and systemic inflammation in chronic injury of the ACL by the detection of systemic and local cytokines, by the activity of MMP-9 and by the inflow of neutrophils. There were interactions between systemic and local cytokines, in which a cytokine did not always exert the same function in the serum as in the synovial fluid. The interleucines (IL) connected to degradation of the cartilage in chronic injury of the ACL were IL-12, IL-6 and IL-8, and those connected to pain and loss of function were IL-6 and IL-9. In counterpart, MMP-2 showed a negative correlation with the damage to the cartilage. It was concluded that the molecules studied had potential as biomarkers, since alterations were suggestive of injury and degradation of the cartilage. In addition, after the traumatic event resulting in rupture of the ACL, the ambient remained chronically inflamed and this inflammation was crucial for the high index of posttraumatic OA.